Few Layer Graphene sticking by biofilm of freshwater diatom Nitzschia palea as a mitigation to its ecotoxicity. (March 2017) - Garacci, M.; Barret, M.; Mouchet, F.; Sarrieu, C.; Lonchambon, P.; Flahaut, E.; Gauthier, L.; Silvestre, J.; Pinelli, E.
Abstract: Carbon-based nanoparticles such as graphene have many applications leading to their industrial production. Few-Layer Graphene (FLG) is thus likely to be found in the environment, and especially in rivers. In this study, the effect of FLG on the photosynthetic benthic diatom Nitzschia palea was assessed making distinction between the impact of a direct contact with FLG and a shading effect of FLG on diatoms. Growth inhibition of diatoms exposed to FLG at 50 mg L −1 was observed at 48 h of exposure associated with an increase in diatoms mortality. At 144 h, the growth rate was recovered. However, in shading condition, at 48 h of FLG exposure, a persistent growth inhibition was observed at 50 mg L −1 . Microscopic observations and a monitoring of FLG concentration in the medium allowed to conclude that exo-polymeric substances (EPS), naturally secreted by N. palea, strongly interact with FLG, sticking nanoparticles at the bottom of wells. Our results highlight the potential mechanisms of clarification of the water column by diatoms biofilms, by sticking FLG even at high concentration. Overall, these results suggest that one potential toxicity process of graphene could be a combination of direct and shading effect leading to a strong interaction between biofilm and nanoparticles. Graphical abstract: